Natural Protein Films from Textile Waste for Wound Healing and Wound Dressing Applications - Livia Ottaviano; Sara Buoso; Roberto Zamboni; Giovanna Sotgiu; Tamara Posati (Journal of Functional Biomaterials)
In recent years, several studies have focused on the development of sustainable, biocompatible, and biodegradable films with potential applications in wound healing and wound dressing systems. Natural macromolecules, particularly proteins, have emerged as attractive alternatives to synthetic polymers due to their biocompatibility, biodegradability, low immunogenicity, and adaptability. Among these proteins, keratin, extracted from waste wool, and fibroin, derived from Bombyx mori cocoons, exhibit exceptional properties such as mechanical strength, cell adhesion capabilities, and suitability for various fabrication methods. These proteins can also be functionalized with antimicrobial, antioxidant, and anti-inflammatory compounds, making them highly versatile for biomedical applications. This review highlights the promising potential of keratin- and fibroin-based films as innovative platforms for wound healing, emphasizing their advantages and the prospects they offer in creating next-generation wound dressing devices.